Meningkatkan Pemahaman Peserta Didik Pada Mata Kuliah Kajian Matematika SMP dengan Metode Tutor Sebaya Melalui Diskusi Kelompok Dalam Kegiatan LSLC - Purwati Purwati; Jeinne Mumu; Benidiktus Tanujaya (JURNAL EKSAKTA PENDIDIKAN (JEP), 2018)
This research was the qualitative research that aimed to improve students understanding of junior high mathematics study. In accordance with the object to be studied, then this research is done in 3 times open class consisting of the plan, do, and see for each cycle, with the subject of research was the students of mathematics education department of FKIP UNIPA whom contracting subjects junior mathematics studies. To improve students understanding of the material, implementation of peer tutor methods was continuously modified based on the findings of each cycle. Based on the results of the implementation of Lesson Study as much as 3 cycles obtained the concluded that the learning outcomes of learners used peer tutor approach that modified each cycle has a significant increase. This was evident from students who answered the test correctly given at the end of each meeting. In the first cycle, from 27 students only 4 who can answer the test correctly that is equal to 14.81%, the second cycle, from 27 learners only 10 which was able to answer the test correctly that was equal to 37,04%, whereas in cycle III, from 26 students 21 students able to answer correctly that was equal to 80,77%